CONNECTING ENVIRONMENTAL, ADMINISTRATION, AND DIRECT CARE FACTORS AFFECTING PATIENT-CENTERED CARE. (11th November 2018) - Dannewitz, H; Stratton, L; Margrett, J; Brown, L; Shelley, M
Abstract: The Targeted Training Intervention 360 (TTI 360) program, led by the Alzheimer's Association, aims to improve quality of care for persons with dementia (PWD) living in Iowa long-term care communities. TTI provides training to administrators (n=10) and direct care professionals (n=45) at 10 participating facilities in Iowa. TTI employs the Experiential Model of Dementia, which focuses on the unmet needs of PWD to increase person-centered care. Data were collected from a pre-test given at the training sessions. An organization's patient-centered care level was measured using the Person Centered Care Assessment tool (P-CAT). Administrators and their employees were asked to decide the degree to which they believed the statements corresponded to their own experiences within the organization. Participants were split in to three groups for purposes of data analysis: -direct care professionals, directors of nursing, and administrators. An analysis of variance model revealed that administrators endorsed significantly greater person-centered care support (Mean = 48) compared to direct care professionals (M = 42; p=.002). Perceptions of person-centered care were positively related to CMS rating. The results demonstrate that the participating administrators may be disconnected from the reality of care on the ground level of their organizations. Methods that are used to bolster person-centered care and improve the quality of care will be discussed.